1988
DOI: 10.1007/bf03010543
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects of induction of epidural analgesia in labour

Abstract: p < 0.05). and in SBP , DBP , Impairment of uterine blood flow (UBF) during labour is an hnportaul cause of fetal asphyxia and neonatal mortality and morbidity. Direct measurement of UBF in humans, requiring either vascular canuulation or radio-isotope techniques, is limited by ethical considerations. Since UBF is a component of maternal cardiac output (CO), investigation of the relationships between maternal CO and blood pressure (BP) is central to understanding the factors which influence uterine blood flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
2
8
0
1
Order By: Relevance
“…We designated this preterm labour group as the primary control group that controlled for the largest number of confounders because all pre‐eclamptic patients were receiving magnesium sulphate. Another potential confounder was the effect of epidural analgesia 19,20 . Here we compared unanesthetised normal labouring patients (secondary control group A) to those receiving continuous epidural analgesia (secondary control group B), and no haemodynamic differences were noted, thus eliminating epidural anaesthesia as a confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…We designated this preterm labour group as the primary control group that controlled for the largest number of confounders because all pre‐eclamptic patients were receiving magnesium sulphate. Another potential confounder was the effect of epidural analgesia 19,20 . Here we compared unanesthetised normal labouring patients (secondary control group A) to those receiving continuous epidural analgesia (secondary control group B), and no haemodynamic differences were noted, thus eliminating epidural anaesthesia as a confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…When epidural anesthesia was assessed in patients in the lateral decubitus position, previous authors reported a decrease in cardiac output and mean arterial pressure starting approximately 30 min after anesthesia, followed by a return to baseline 45 min after anesthesia 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Although this increase is mainly due to a rise in stroke volume, the heart rate changes will also affect the cardiac output response to labor. The increase in cardiac output during labor is generally thought to result from anxiety and pain and this is supported by the observation that cardiac output increases less in the presence of any form of analgesia 4,5 . Labor and delivery obviously represent a period of considerable additional hemodynamic demands.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations